The Production of Threadfin Bream (Nemipterus Japonicus) Protein Hydrolysate by Hydrolysis with Alcalase - Ismail, Normah (2001)
The optimization of hydrolysis conditions in terms of pH, temperature, enzymesubstrate (ES) ratio and hydrolysis time for the production of threadfin bream (Nemipterus japonicus) hydrolysate was studied. Alcalase showed a higher percent nitrogen recovery (% NR) than Flavourzyme: Protamex mixture. By using Alcalase, the optimum hydrolysis conditions were pH 8.5, 60°C, ES2% and 120 min hydrolysis time. At least twenty percent degree of hydrolysis (% DH) and 70% NR was achieved. The yield of spray-dried hydrolysate hydrolysed under these conditions was 4%. The hydrolysate was white in color, highly soluble over a wide pH range, high in protein and essential amino acids but low in fat. The hydrolysate also exhibited an improvement in foam ability in comparison to the threadfin bream muscle but the foam was unstable. Hydrolysis with Alcalase also produced hydrolysate with poor emulsifying properties. The major free amino acids in the hydrolysate were glutamic acid,aspartic acid, lysine, leucine and arginine in which glutamic acid was the dominant amino acid. Bitter amino acids methionine, valine, isoleucine, phenylalanine, leucine, arginine and tyrosine comprised of 42.34% of the total free amino acids. The inosine 5'-monophosphate (IMP) content was higher in the hydrolysate than that in the muscle. SDS-PAGE showed the presence of twenty peptide bands in the muscle having molecular weight between 7.2 to 87.6 kD and thirteen in the hydrolysate with molecular weight between 7.2 to 64 kD. For Sephadex G-75 fractions (FR), no peptide bands were seen in FR I, III, IV, VI, VII and VIII. FR II and V showed the presence of respectively five and seven peptide bands with molecular weight between 11.4 to 54 kD and 10.5 to 51.3 kD. Histamine content in the muscle was found to be 14.45 mgkg 1 but no histamine was detected in the hydrolysate. Sensory evaluation of the hydrolysate indicated that it was fishy in flavor and constitutes three basic tastes namely bitter, umami and salty with umami and bitterness as the dominating tastes.